已知数列{an}满足递推关系式:an+2an-an+12=tn(t-1),(n∈N*),且a1=1,a2=t.(t为常数,且t>1)
(1)求a3;
(2)求证:{an}满足关系式an+2-2tan+1+tan=0,(n∈N*;
(3)求证:an+1>an≥1(n∈N*).
(1)由a3a1-a22=t(t-1)和a1=1,a2=t
∴a3=2t2-t…(4分)
(2)由an+2an-an+12=tn(t-1),(n∈N*)
得an+1an-1-an2=tn-1(t-1)(n≥2),
再由上两式相除得到:∴an+2an-an+12=tan+1an-1-tan2
∴an(an+2+tan)=an+1(an+1+tan-1)
∴
=an+2+tan an+1 an+1tan-1 an
即{
}为常数列an+2+tan an+1
∴
=an+2+tan an+1 a3+ta1 a2
而a3+ta1=2t2∴
=2t.an+2+tan an+1
即an+2-2tan+1+tan=0.…(9分)
(3)由t>1知:an+2an>an+12≥0
∴an+2an>0
故an+2与an同号
而a1=1>0,a2=t>0.
故an>0.
又a
+2an>• n a 2n+1
即
>an+2 an+1 an+1 an
∴
>an+1 an
>…>an an-1
=t>1a2 a1
∴an+1>an
∴an≥1
∴an+1>an≥1.…(14分)